Improved Right Ventricular Performance with Increased Tricuspid Annular Excursion in Athlete’s Heart - Zha, Wei; Schiros, Chun G.; Reddy, Gautam; Feng, Wei; Denney, Thomas S.; Lloyd, Steven G.; Dell’Italia, Louis J.; Gupta, Himanshu (Frontiers in Cardiovascular Medicine, 2015)
Background: Marathon runners (MTH) and patients with mitral regurgitation (MR) exhibit left ventricular (LV) overload, and LV geometric changes in these groups have been reported. In this study, right ventricular (RV) adaptation to chronic volume overload was evaluated in MTH and MR and normal controls together with interventricular septal remodeling and tricuspid annulus (TA) motion. Methods: A total of 60 age-matched subjects (including 19 MTH, 17 isolated chronic compensated MR patients and 24 normal subjects) underwent conventional cine and tagged cardiac magnetic resonance imaging. Myocardial strain and curvature were computed on the interventricular septum and RV free wall. A dual-propagation technique was applied to construct RV volume-time curves for a single cardiac cycle. Similarly, the tricuspid annulus was tracked throughout the cardiac cycle to create displacement over time curve. Results: Septal curvature was significantly lower in MTH and MR compared to controls. No significant differences in RV free wall strain or RV ejection fraction were noted amongst the 3 groups. However, longitudinal TA excursion was significantly higher in MTH compared to controls (p=0.0061). The peak late diastolic TA velocity in MR was significantly faster than MTH (p=0.0031) and controls (p=0.020). Conclusions: Increased TA kinetics allows for improved RV performance in MTH. Septal remodeling was observed in both MR and MTH, therefore a direct relationship of septal remodeling to TA kinetics in athlete’s heart could not be elucidated in this study.